A family of 3D UO22+–5-X-1, 3-dicarboxylate (X = –H, –NO2, –NH2, –OH) hybrid materials: structural relevance with variation of substituent groups and photochemical properties1. Issue 11 (21st March 2015) - Zhai, Xiang-Sheng; Zhu, Wen-Gang; Xu, Wei; Huang, Ya-Jing; Zheng, Yue-Qing
<x xml:space="preserve">Abstract</x> A family of 3D uranyl hybrid materials based on 5-X-1, 3-dicarboxylate have been synthesized, in which two types of 1D chains assembled by the same uranyl dimer motif [(UO2)2L2] exist.